2022
DOI: 10.1108/imr-10-2021-0291
|View full text |Cite
|
Sign up to set email alerts
|

The interaction effect of country-of-origin positioning and cultural distance on international advertising effectiveness: a construal level perspective

Abstract: PurposeThis research draws upon construal level theory to investigate how brands can develop effective international marketing strategies using country image versus product image across international markets with different cultural distances between them.Design/methodology/approachThe paper reports two preliminary studies and three experimental studies in the context of Australian brands using a “clean and green” image. The preliminary studies explore how product versus country image and cultural similarity ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 80 publications
(218 reference statements)
0
7
0
Order By: Relevance
“…Finally, we have demonstrated that our effects are consistent across different markets (India, the US and the UK). However, we note that these markets also have cultural differences (Septianto et al, 2022). As such, future research could explore the extent to which our effect could be extended across different international markets and the potential cultural dimensions that may influence the identified effects.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 90%
“…Finally, we have demonstrated that our effects are consistent across different markets (India, the US and the UK). However, we note that these markets also have cultural differences (Septianto et al, 2022). As such, future research could explore the extent to which our effect could be extended across different international markets and the potential cultural dimensions that may influence the identified effects.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 90%
“…It has been found that consumers use their knowledge or stereotypes they hold about a country and use such knowledge to evaluate brands they perceive to be associated with that country (Balabanis et al , 2019). For example, Septianto et al (2022, p. 1) argues that “an Australian brand emphasizing the country's image gain low favourable responses among consumers”. Additionally, consumers perceived world from a categorical perspective to “economize their cognitive resources and simplify and/or streamline their underlying cognitive processes” (Balabanis et al , 2019, p. 42).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Seeing COO as providing important information for consumer decision making has long been accepted by researchers (e.g. Bilkey and Nes, 1982;Han, 1989;Hong and Wyer 1990;Phau and Chao, 2008;Phau and Prendergast, 2000;Septianto et al, 2022;Schill et al, 2021;Verlegh and Steenkamp, 1999). It is so important a consideration for the consumers, to the extent that during the COVID-19 pandemic, COO has appeared to be an important factor in the vaccine choice (Chaney and Lee, 2022).…”
Section: Literature Review and Hypotheses Development Country-of-orig...mentioning
confidence: 99%
“…Seeing COO as providing important information for consumer decision making has long been accepted by researchers (e.g. Bilkey and Nes, 1982; Han, 1989; Hong and Wyer 1990; Phau and Chao, 2008; Phau and Prendergast, 2000; Septianto et al. , 2022; Schill et al.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%